(untitled) ("Journal "U". Economy. Management. Finance.", 2018)
The article defines the economic role of transport. The transport system is the importance of as an essential component of the material basis of the economy of any country. Automated systems of non-cash payment for travel are presented in the article as the way of functioning of transport enterprises in the modern conditions.